2018
DOI: 10.3389/fnins.2018.00034
|View full text |Cite
|
Sign up to set email alerts
|

Hurst Exponent Analysis of Resting-State fMRI Signal Complexity across the Adult Lifespan

Abstract: Exploring functional information among various brain regions across time enables understanding of healthy aging process and holds great promise for age-related brain disease diagnosis. This paper proposed a method to explore fractal complexity of the resting-state functional magnetic resonance imaging (rs-fMRI) signal in the human brain across the adult lifespan using Hurst exponent (HE). We took advantage of the examined rs-fMRI data from 116 adults 19 to 85 years of age (44.3 ± 19.4 years, 49 females) from N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 49 publications
2
58
0
Order By: Relevance
“…In an initial analysis performed on the entire HCP dataset (n=1003), we found that 725 regions (out of 1114 across seven atlases) exhibited significant sex differences in HE. The regions identified in this analysis matched those previously observed [3]. However, upon repeating the analysis on the grey-matter volume matched subset (n=390) to eliminate the effects of volumetric differences, we found that only a subset of the originally identified regions were significantly different between males and females.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…In an initial analysis performed on the entire HCP dataset (n=1003), we found that 725 regions (out of 1114 across seven atlases) exhibited significant sex differences in HE. The regions identified in this analysis matched those previously observed [3]. However, upon repeating the analysis on the grey-matter volume matched subset (n=390) to eliminate the effects of volumetric differences, we found that only a subset of the originally identified regions were significantly different between males and females.…”
Section: Discussionsupporting
confidence: 71%
“…However, upon repeating the analysis on the grey-matter volume matched subset (n=390) to eliminate the effects of volumetric differences, we found that only a subset of the originally identified regions were significantly different between males and females. This suggests that previous results [3] may be confounded by volume differences and these differences must be accounted for when analysing sex differences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since early demonstrations of using the Hurst exponent from the toolbox of chaos theory and fractals to analyse fMRI BOLD signal complexity (e.g., [7,8,9]), interest has grown in this novel method for characterizing complexity of fMRI activation. The Hurst exponent has been applied to many domains of research including Alzheimer's disease [10], signal complexity change over the adult lifespan [11], distress related to medical treatment [12], task versus rest states [13], and alcohol-induced intoxication versus non-intoxicated states [14]. Other measures of complexity such as functional variability have also demonstrated meaningful real-world associations (e.g., children develop more complex brain activity with age, see [15]).…”
Section: Introductionmentioning
confidence: 99%